SAUNA AS A CATALYST FOR HEALTH: MULTIFACETED BENEFITS OF THERMOTHERAPY IN ENHANCING CARDIOVASCULAR, ENDOCRINE, AND IMMUNE FUNCTIONS - Kacper Rozenberg,; Justyna Stryjecka,; Karolina Niewola,; Martyna Różańska, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: A growing body of research suggests that regular sauna use is associated with a range of health benefits. Observational studies indicate positive effects on multiple physiological systems, but the mechanisms underlying these effects require further investigation.Aim of the Study: This study aims to systematically review and analyze scientific literature on the health effects of regular sauna use. The focus is on its impact on the cardiovascular system (including mortality risk and lipid profiles), mental health (symptoms of depression and anxiety), the immune system (inflammatory markers and immune cell activity), the endocrine system (levels of cortisol, adrenaline, and prolactin), the respiratory system, and skin health.Methodology: This review synthesizes data from scientific publications on thermotherapy via sauna use. Studies were selected for their relevance and methodological quality. Articles lacking scientific rigor were excluded. The literature search included databases such as PubMed and Google Scholar, prioritizing systematic reviews and longitudinal studies.Results: The review found a strong association between regular sauna use and reduced cardiovascular mortality. Positive effects were also seen in lipid profiles, reductions in depression and stress symptoms, and modulation of immune responses (e.g., lower inflammatory markers). Potential benefits were noted for respiratory and skin health. Endocrine responses were complex, with thermal stress increasing cortisol and catecholamine levels, and possible changes in growth hormone.Conclusions: Regular sauna use may serve as a simple, accessible method to support health and prevent disease. Nonetheless, risks like dehydration and overheating must be considered. Further research is essential to clarify mechanisms and optimize therapeutic use.